Synthesis of (5R*,6R*)-6-(3-(tert-Butyldimethylsilyloxy)prop-1-ynyl)-5-hydroxypiperidin-2-one - Duc, Dau Xuan; Dung, Vo Cong (Vietnam Journal of Science and Technology, 2017)
The synthesis of racemic (5R*,6R*)-6-(3-(tert-Butyldimethylsilyloxy)prop-1-ynyl)-5-hydroxypiperidin-2-one was accomplished in 10.3% overall yield over 7 steps. The key steps involved a Sonogashira coupling reaction to make an ene-yne ester and an azidolysis reaction of an epoxide ester to form a γ-lactone.